Trade liberalisation, process and product innovation, and relative skill demand - Sebastian Braun (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
The interaction between trade liberalisation, product and process innovation, and relative skill demand is analysed in a model of international oligopoly. Lower trading barriers increase the degree of foreign competition. The competing enterprises respond by investing more aggres- sively in lowering marginal costs of production. Moreover, firms reduce the substitutability of their products through additional investment in product innovation. The paper also shows that the relative demand for skilled workers may increase as a result.
Keywords: F12; F15; F16; O32; 330; Intra-industry Trade; Process Innovation; Product Innovation; Relative Skill Demand; Trade Liberalisation; Intraindustrieller Handel; Außenhandelsliberalisierung; Internationaler Wettbewerb; Oligopol; Innovation; Arbeitsnachfrage; Qualifikation; Theorie